PEMANFAATAN MEDIA TEKNOLOGI INFORMASI SEBAGAI AKSES MENINGKATKAN MUTU PENDIDIKAN DALAM PERSAINGAN DUNIA PENDIDIKAN DI ERA GLOBAL - Fatmawati, Fatmawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Information Technology today has become a fundamental need for educational institutions. Through the utilization of information technology as a medium of learning, school institutions are expected to be able to improve the quality of learning through access to information technology to develop learning media. This research was conducted at SD Negeri 26 Rimau Island. This study used qualitative research methods. Data collection techniques used observation, interviews and documentation. Data analysis used interactive analysis of Miles and Huberman models. The results of this study is the use of learning media using Information Technology to develop curriculum in schools that direction toward improving the quality of education. The use of this media requires preparations such as human resources such as the readiness of teachers, students and parents. The use of learning media is expected to improve teaching and learning process in teachers and students, can be more effective, efficient, and encourage student creativity. Another advantage is the cost savings of operational learning and facilitate the preparation of teachers in teaching. In addition, it will facilitate the assessment, overcome the limitations of learning media that are not available, and hope to improve student knowledge. Keyword: Information technology, Learning Media, Quality Improvement